RESTORAN DENGAN KONSEP SUSTAINABLE DESIGN - Achmad Linggar Bagaskara; Gervasius Herry Purwoko; Maria Y. Susan (KREASI, 2016)
Human as social being require a place where they can gather and interact each other. With that kind of space, they can improve or increase the life quality of every individual, or maybe it will add a new value for them. A restaurant is an example where people can gather and interact. The Garden Space is a restaurant with a concept to improve social and environment quality. So the design should answer and supporting restaurant’s concept. Sustainable design’s principle applied to support restaurant’s value of social and environment. The the architecture and interior design was inspired by the beauty of the modern contemporary design and it can be seen on the outside and inside the building. Skylights are designed to reduce the use of artificial lighting on midday and afternoon. Rainwater storage is used to minimise the use of water, and it is applied in the toilet’s urinal. There is also a hydroponic garden, a place where customer will be educated and they can interact with nature.